A DFT+U Based Study of Full‐Heusler Alloy Ru2VSi. Issue 1 (23rd February 2023) - Kapil, Jyoti; Shukla, Pramila; Pathak, Ashish
Abstract: In this paper, the structural, electronic, magnetic, and elastic properties of Full‐Heusler alloy Ru2 VSi are studied using density functional theory (DFT) by implementing Hubbard correction parameter (U). The calculations are performed using Generalized Gradient Approximation (GGA) with and without implementation of U and the results are compared. With GGA only, the compound shows a metallic behavior with the overlapping of bands in both the up and down spin states and exhibits a non‐integral magnetic moment. With the incorporation of U, the alloy shows a half‐metallic behavior with a finite indirect band‐gap of 0.51 eV in the spin‐down state and a metallic character in the spin‐up state. It also shows an integral magnetic moment of 1.00 μB, in good agreement with the Slater‐Pauling Rule for half‐metallicity in Full‐Heusler alloys. The elastic properties indicate toward the stability of this compound against external stresses and deformations. The observed properties make this compound a suitable material for applications based on spintronic devices.